DRIVING SUSTAINABLE OPERATIONAL PERFORMANCE THROUGH GREEN OPERATIONS AND COST EFFICIENCY: THE MEDIATING ROLE OF CORPORATE REPUTATION - Syamrul Syamrul; Nuralfania Nuralfania; Prof. Dr. H. Mahfudnumajamuddin, SE.,MM; Prof. Dr. Serlin Serang, SE.,M.Si (Accounting Profession Journal (APAJI), 2026)
This study examines the relationships between green operations, cost efficiency, corporate reputation, and sustainable operational performance within small and medium-sized enterprises (SMEs) in Indonesia. Using a quantitative approach, data were collected from 195 managerial-level respondents across four major cities and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that green operations have a positive and significant direct effect on sustainable operational performance, highlighting their role as an internal driver of sustainability. In contrast, cost efficiency does not directly influence sustainable performance but significantly affects corporate reputation. Furthermore, corporate reputation is found to have a strong positive effect on sustainable operational performance and mediates the relationship between cost efficiency and performance. However, it does not mediate the relationship between green operations and performance. These results indicate the existence of dual pathways, where green operations enhance performance internally, while cost efficiency operates through reputational mechanisms. The study contributes to the literature by offering a nuanced understanding of how operational strategies translate into sustainability outcomes and provides practical insights for managers in aligning efficiency and environmental initiatives.